2023
DOI: 10.1177/09544062231163427
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the performance of continuous solar-powered adsorption refrigeration system for optimal use in Zaria, Nigeria

Abstract: Cooling without electricity is the reason for solar adorption refrigeration systems. The epileptic power supply, especially in developing countries, makes solar refrigeration a very attractive option. This is coupled with the abundance of solar energy, making it a favourable alternative power source amongst other power mixes. This article introduces a solar adsorption refrigerator that continually generates cooling using solar energy as a standalone. Thus, this study aims to simulate and analyse the feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Physical working pairs (PWP) rely on van der Waals forces to capture and retain the adsorbate. Examples of physical working pairs include zeolite with water (Sowunmi et al, 2023) by utilizing the TRNSYS 16.0 simulation software, model, assess the viability of refrigeration from a system that employs a combination of zeolite-based adsorbents and water (H2O) as adsorbate pairs via four solar concentrating collectors, two for adsorption and two for desorption. Patel & Maiti, (2023) reported that the solar adsorptioncooling machine with zeolite13X-water as an adsorbentadsorbate pair was designed, fabricated, and experimentally investigated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Physical working pairs (PWP) rely on van der Waals forces to capture and retain the adsorbate. Examples of physical working pairs include zeolite with water (Sowunmi et al, 2023) by utilizing the TRNSYS 16.0 simulation software, model, assess the viability of refrigeration from a system that employs a combination of zeolite-based adsorbents and water (H2O) as adsorbate pairs via four solar concentrating collectors, two for adsorption and two for desorption. Patel & Maiti, (2023) reported that the solar adsorptioncooling machine with zeolite13X-water as an adsorbentadsorbate pair was designed, fabricated, and experimentally investigated.…”
Section: Literature Reviewmentioning
confidence: 99%